Kategorisasi Kemampuan Literasi Matematika Siswa SMP Negeri Se-Kota Kupang Berbantuan Fuzzy Inference System Metode Mamdani - Daniel W. Fointuna; Agapitus H. Kaluge; Aloysius Joakim Fernandez (Program Studi Pendidikan Matematika Universitas Katolik Widya Mandira, 2019)
This survey aims to describe the mathematical literacy of state junior high school students in Kupang city, East Nusa Tenggara province. It was done not only due to the low achievement of Indonesian 15-year-old students in PISA but also because there are no surveys which had been done before to map the mathematical literacy of students in Kupang city. A total of 377 respondents who were the ninth grade students representing six state junior high schools in Kupang were collected by two-stage cluster randomized sampling. The students were assessed using fifteen problems adopted from PISA 2012 and some development researches with a product of mathematical literacy problems so that those items were highly reliable to measure students mathematical literacy. The categorization of students mathematical literacy was carried out using Mamdani’s Fuzzy Inference method. The input of fuzzification was a score of three process domains assessed by those fifteen problems, specifically formulating, employing, and interpreting. The output of defuzzification was students mathematical literacy score used to determine the category of students mathematical literacy. The results showed that the mathematical literacy of state junior high school students in Kupang city was generally classified as a low category.